Rotavirus and adenovirus gastroenteritis: time series analysis. Issue 4 (28th April 2015) - Celik, Cem; Gozel, Mustafa Gokhan; Turkay, Hakan; Bakici, Mustafa Zahir; Güven, Ahmet Sami; Elaldi, Nazif
Abstract Background This study investigated the effects of changes in weather conditions (monthly average temperature, monthly minimum temperature, monthly average humidity) on rotavirus and adenovirus gastroenteritis frequency and whether there was a seasonal correlation. Methods Between 2006 and 2012, 4702 fecal samples were taken from patients ≤5 years of age with acute gastroenteritis; these samples were analyzed in terms of rotavirus group A and adenovirus serotype 40–41 antigens using time‐series and negative binomial regression analysis. Results Rotavirus antigens were found in 797 samples (17.0%), adenovirus antigens in 113 samples (2.4%), and rotavirus and adenovirus antigens together in 16 samples (0.3%). There was a seasonal change in rotavirus gastroenteritis (P < 0.001), and a 1°C decrease in average temperature increased the ratio of rotavirus cases in those with diarrhea by 0.523%. In addition, compared with data from other years, the number of patients was lower in the first month of 2008 and in the second month of 2012, when the temperature was below −20°C (monthly minimum temperature). There was no statistically significant relationship between adenovirus infection and change in weather conditions. Conclusion Various factors such as change in weather conditions, as well as the population's sensitivity and associated changes in activity, play a role in the spread of rotavirus infection.